Water depercolation of setting cement paste evaluated by diffuse ultrasound. (August 2016) - Yim, Hong Jae; An, Yun-Kyu; Kim, Jae Hong
Abstract: Microstructural evolution during setting of cement-based materials explains its solidification. While various studies have attempted to reveal the microstructural evolution, many questions still remain. The setting process refers to the phase change from a cement suspension to a poroelastic solid. This study proposes a diffuse ultrasound method to investigate microstructural evolution and to determine the setting of cement paste. The diffuse ultrasound refers the propagation of an incoherent component on P-waves through-transmission. Its velocity and attenuation reflect the tortuous paths in early-age cement paste. Closing the tortuous paths by cement hydration and coagulation causes the diffuse ultrasound to combine with the propagated P-wave. The combined time is then an indicator of the setting point. The diffusivity, dissipation, and permeability evaluated by the diffuse ultrasound also shed light on the microstructural evolution of fresh cement paste.